2023
DOI: 10.1002/cne.25444
|View full text |Cite
|
Sign up to set email alerts
|

Catecholaminergic axon innervation and morphology in flat‐mounts of atria and ventricles of mice

Abstract: Sympathetic efferent axons regulate cardiac functions. However, the topographical distribution and morphology of cardiac sympathetic efferent axons remain insufficiently characterized due to the technical challenges involved in immunohistochemical labeling of the thick walls of the whole heart. In this study, flat-mounts of the left and right atria and ventricles of FVB mice were immunolabeled for tyrosine hydroxylase (TH), a marker of sympathetic nerves. Atrial and ventricular flat-mounts were scanned using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 76 publications
2
4
0
Order By: Relevance
“…11 and ), ICG neurons were clustered together following CIH compared to RA. Similar to our recent study (Bizanti et al., 2023; Zhang et al., 2023), and in contrast to vagal efferent axons, TH‐IR axons were seen to travel through TH‐IR neurons in the ganglia rather than tightly encircle individual neurons. TH‐IR axons coursing through ICG were observed in the optical sections (Fig.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…11 and ), ICG neurons were clustered together following CIH compared to RA. Similar to our recent study (Bizanti et al., 2023; Zhang et al., 2023), and in contrast to vagal efferent axons, TH‐IR axons were seen to travel through TH‐IR neurons in the ganglia rather than tightly encircle individual neurons. TH‐IR axons coursing through ICG were observed in the optical sections (Fig.…”
Section: Resultssupporting
confidence: 91%
“…Consistent with our previous studies (Bizanti et al., 2023), we observed that TH‐IR bundles and axons primarily travelled through the ICG without encircling individual ICG principal neurons as seen by parasympathetic axons in RA after CIH (Cheng, 2017). The consistent distribution of ICG was evident, with most ganglia noted in the left atrial region.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Hearts along with the lungs and trachea were removed from the chest and postfixed overnight in 4% paraformaldehyde at 4 °C. The heart was placed and pinned into a dissecting dish lined with Sylgard and containing PBS (0.1 M, pH = 7.4), and the specimen was further dissected using a Leica Stereo microscope as described previously 25,27,28,32,33 . To reveal the intact network of sympathetic postganglionic atrial innervation, we removed the heart from the surrounding tissues (lungs, aortic arch and trachea).…”
Section: Tissue Preparationmentioning
confidence: 99%